Breaking barriers: exploring physiotherapists' willingness and challenges in embracing telerehabilitation in a developing country - Erturan, Sinem; Burak, Mustafa; Elbasan, Buelent (Springer London Ltd, 2024)
IntroductionTelerehabilitation (TR) is an innovative approach that can address the limited availability and restricted access to rehabilitation services, particularly during challenging times such as pandemics and natural disasters. This study focuses on understanding the desires, perceptions, and barriers that physiotherapists face when implementing TR in a developing country.MethodThe study was conducted with 219 physiotherapists residing in a developing country using a web-based survey on Google Docs.ResultThe findings revealed that a significant majority of physiotherapists (88.1%) recognized TR as a potential solution for individuals with physical problems during the pandemic. Additionally, 89.5% expressed satisfaction with the opportunity to receive consultations from different hospitals, indicating a positive perception of TR. However, the study also highlighted certain barriers that hindered the implementation of TR. Around 40.2% of physiotherapists reported having training deficiencies, suggesting a need for educational support in utilizing TR effectively. Furthermore, the analysis of demographic factors revealed interesting insights. It was noteworthy that the age and years of experience of physiotherapists had an impact on their willingness and adoption of TR.ConclusionThe study reveals that physiotherapists in the developing country exhibit a positive attitude towards TR and recognize its potential benefits. However, various barriers, such as training deficiencies, need to be addressed to facilitate a broader adoption of TR in their practices. Overcoming these barriers is anticipated to heighten physiotherapists' readiness to embrace TR, ultimately enhancing the accessibility and delivery of rehabilitation services.
Keywords: Barriers; Musculoskeletal diseases; Neurological rehabilitation; Physiotherapy; Telerehabilitation